Hubungan Gaya Mengajar Dengan Profesionalitas Guru: Survey Di SMK Teratai Putih Jakarta - Muhammad Hisyam Zakariya; Yayat Suharyat (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2012)
This study aims to determine the relationship between teaching styles with the professionalism of teachers in SMK Teratai Putih Jakarta. The method used is survey method with the correlation approach. This study connects the teaching style as a variable X and the professionalism of teachers as the variable Y. The population in this study was students in class X and XI SMK Teratai Putih Jakarta as many as 300 students, while the sample in this study of 50 students is calculated by the formula Slovin and drawn by Simple Random Sampling. The results showed that there is a positive relationship between teaching style with the professionalism of teachers in SMK Teratai Putih Jakarta, with the regression Y = a + bx or y = 27.8 + 0.678 x and test coefficient 0.3481 determinant of this suggests that the professionalism of teachers 34.81% contributed by the style of teaching. The results of significance testing (test T) to the value of r was obtained by 0.59 significance at α = 0.05 with a Table count = 5.109 = 1.684, then significant. It can be concluded that the hypothesis that there is a relation or a positive correlation between teaching style relationship with the professionalism of teachers